2021
DOI: 10.3389/fcell.2021.616580
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Proteins Confer Cell Adhesion-Mediated Drug Resistance Through Integrin αv in Glioblastoma Cells

Abstract: Chemotherapy resistance to glioblastoma (GBM) remains an obstacle that is difficult to overcome, leading to poor prognosis of GBM patients. Many previous studies have focused on resistance mechanisms intrinsic to cancer cells; the microenvironment surrounding tumor cells has been found more recently to have significant impacts on the response to chemotherapeutic agents. Extracellular matrix (ECM) proteins may confer cell adhesion-mediated drug resistance (CAMDR). Here, expression of the ECM proteins laminin, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…[9,14,16,[45][46][47][48] Hydrogels have been widely implemented to develop tissue engineered constructs that mimic various aspects of the tumor microenvironment. [5,[19][20][21][22][23][24][25][26][27][28][29] For instance, natural hydrogels have been implemented to model the tumor microenvironment using proteins such as collagen, gelatin, and fibrin and polysaccharides such as hyaluronic acid and alginate have been incorporated to produce semi-synthetic hydrogels. [49][50][51] While these hydrogels provide relevant biochemical properties, batch to batch variability, viscosity, and limitations concerning independent control of mechanical and biochemical properties are often challenging obstacles to overcome with when using these materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,14,16,[45][46][47][48] Hydrogels have been widely implemented to develop tissue engineered constructs that mimic various aspects of the tumor microenvironment. [5,[19][20][21][22][23][24][25][26][27][28][29] For instance, natural hydrogels have been implemented to model the tumor microenvironment using proteins such as collagen, gelatin, and fibrin and polysaccharides such as hyaluronic acid and alginate have been incorporated to produce semi-synthetic hydrogels. [49][50][51] While these hydrogels provide relevant biochemical properties, batch to batch variability, viscosity, and limitations concerning independent control of mechanical and biochemical properties are often challenging obstacles to overcome with when using these materials.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that cell-ECM interactions play a key role in governing cancer cell fate. [5,[19][20][21][22][23][24][25][26][27][28][29] In this context, we previously developed sixteen unique hydrogel formulations composed of three components: (1) proteolytically degradable PEG (PEG-PQ), (2) integrin ligating PEG-RGDS, and (3) a nondegradable crosslinker NVP. By systematically tuning the concentration of PEG-RGDS and NVP, hydrogel adhesivity and degradability were varied, inducing different phenotypes in the parental triple negative breast cancer line (MDA-MB-231) and three of its organotropic sublines (BRM2a-831s, LM2-4175s, BoM-1833s).…”
Section: Hydrogel Characterizationmentioning
confidence: 99%
“…Integrin activates FAK/paxillin/AKT signaling pathway and affects the expression of the proliferative marker Ki67 in tumors [44]. Recent studies have shown that transmembrane integrin α2β1 directly interacts with lumican, and activates ERK and ALP activities in osteoblasts [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the intrinsic resistance of cancer cells, their high heterogeneity, and the poor drug penetration through the blood-brain barrier, the tumor microenvironment was recently found to significantly impact the response to standard therapies. High levels of vitronectin and fibronectin were detected in clinical GBM tumors and found to confer cell-adhesion-mediated drug resistance [ 65 ]. In this setting, fibronectin suppressed p53-mediated apoptosis and upregulated P-glycoprotein expression, also known as multidrug resistance protein 1 (MDR1), making glioma cells chemoresistant.…”
Section: Role Of Integrin-αvβ3 In Gbm Progressionmentioning
confidence: 99%